2022
DOI: 10.1007/s12144-022-02702-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of personality traits in collaborative group works at flipped classrooms

Abstract: The Flipped Classroom (FC) approach is an important model for individualizing teaching, improving motivation, interaction, and increasing academic performance in a student-centered learning environment. However, at FC, not all students benefit equally from teaching opportunities. There may be important individual differences that affect their academic performance. The relationship between personality traits and academic performance in the FC model in which collaborative group studies are carried out is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…The most striking conclusion of this study is that extraversion is the personality trait with the greatest positive effect on academic success in collaborative FC. This finding demonstrates that students with high extraversion might tend to utilize FC to improve their academic performance [86]. In addition, the research carried out by Komarraju et al among 308 college students showed that students who got higher scores in agreeableness and conscientiousness could get higher GPAs, and the level of neuroticism was negatively related to GPA [87].…”
Section: Academic Performancementioning
confidence: 91%
“…The most striking conclusion of this study is that extraversion is the personality trait with the greatest positive effect on academic success in collaborative FC. This finding demonstrates that students with high extraversion might tend to utilize FC to improve their academic performance [86]. In addition, the research carried out by Komarraju et al among 308 college students showed that students who got higher scores in agreeableness and conscientiousness could get higher GPAs, and the level of neuroticism was negatively related to GPA [87].…”
Section: Academic Performancementioning
confidence: 91%
“…Later, the inside classroom time is used to fill gaps between what has been learned in pre-class tasks and the ability to perform the knowledge which still need guidance or peer collaboration. Students have discussions and presentations with their peers which may enable them to realize, analyze or evaluate different subjects with different perspectives (Yildiz Durak, 2022).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…In the flipped environment, students watch pre‐lesson videos, review documents, or find things out about the course content independently. By doing this, learners need to find solutions with the teacher's support [46, 94, 95]. In the online flipped environment, on the other hand, learners communicate with the teacher digitally, and getting feedback is essential for increasing the quality of learning [93].…”
Section: Conceptual Frameworkmentioning
confidence: 99%